Metodologia para avaliação da vulnerabilidade socioambiental: estudo da cidade de Paracatu (MG) - Rezende, Patrícia Soares (2016)
Nowadays the largest population number is centered in cities and it\'s in them that the urbanization processes occur at an accelerated way, most of times without planning. The use of studies on the socio-environmental vulnerability in an integrated analysis, which contemplates both environmental and social aspects, are considerate an important tool not only to increase knowledge of a particular area, but also to support the decision-making related to environmental issues and their prevention. The chosen study area was the city of Paracatu, located in the northwest of Minas Gerais state, which presents a percentage of 87.08% of people occupying the urban area. The choice of the area is justified by the fact that the city has been presenting an urban expansion and a significant population growth, so that some areas present a disordered occupation, resulting in several socio-environmental problems. Thus, this research aimed to develop a methodology to identify the socialenvironmental vulnerability in the city of Paracatu (MG), using statistical techniques and GIS. The proposed methodology was built from environmental and social variables and to elaborate the indexes statistical techniques were used, as well as GIS and the AHP method. Initially, to diagnose the environmental vulnerability eight variables were considered in which, after the integration through the AHP method, gave origin to the index that highlights areas of the city which are environmentally fragile or that expose the population to risk situations. Posteriorly, through social variables provided by the Demographic Census of 2010 from IBGE, multivariate statistics were used (given the large amount of data) to diagnose the situation of the population in relation to five social factors: education, age, basic sanitation and infrastructure and type of responsible people for the household. After, through the AHP method, the social vulnerability was developed, which shows us the socio-demographic situation of the city. Finally, through the weighted average, the social-environmental vulnerability index was built, integrating the two previous indexes. The last index shows the sectors of the city where there is the concomitant of environmental problems and worse socioeconomic conditions. The results of social-environmental vulnerability showed that the sectors located to the north, northeast and south of the city of Paracatu are the ones which have the greatest vulnerability, because in these regions there is a greater combination of environmental and social problems. These are sectors that require different actions in order to decreasing the vulnerability found and cases of risk, offering better housing, quality of life and even a relocation, when there\'s no alternative left.